2018
DOI: 10.1172/jci99760
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of EZH2 expression in T cells improves efficacy of anti–CTLA-4 therapy

Abstract: Enhancer of zeste homolog 2-mediated (EZH2-mediated) epigenetic regulation of T cell differentiation and Treg function has been described previously; however, the role of EZH2 in T cell-mediated antitumor immunity, especially in the context of immune checkpoint therapy, is not understood. Here, we showed that genetic depletion of EZH2 in Tregs (FoxP3creEZH2fl/fl mice) leads to robust antitumor immunity. In addition, pharmacological inhibition of EZH2 in human T cells using CPI-1205 elicited phenotypic and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
182
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(184 citation statements)
references
References 21 publications
(24 reference statements)
2
182
0
Order By: Relevance
“…For example, selectively blocking FAO or enhancing glycolysis may disrupt Treg stability while promoting anti‐tumour T‐cell function. Perhaps most remarkably, small molecule inhibitors of the chromatin modifier EZH2 may not only reprogramme TI‐Treg function, but also directly increase cytotoxic T‐cell activity and recruitment to the TME (by increasing Th1 chemokine production from tumour cells) . In other instances, targeting some of the pathways described here may have tempered effects due to blocking the function of beneficial immune cell populations attacking the cancer.…”
Section: Conclusion: Key Challenges and Next Stepsmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, selectively blocking FAO or enhancing glycolysis may disrupt Treg stability while promoting anti‐tumour T‐cell function. Perhaps most remarkably, small molecule inhibitors of the chromatin modifier EZH2 may not only reprogramme TI‐Treg function, but also directly increase cytotoxic T‐cell activity and recruitment to the TME (by increasing Th1 chemokine production from tumour cells) . In other instances, targeting some of the pathways described here may have tempered effects due to blocking the function of beneficial immune cell populations attacking the cancer.…”
Section: Conclusion: Key Challenges and Next Stepsmentioning
confidence: 95%
“…Furthermore, anti‐CTLA4 checkpoint blockade dramatically increases EZH2 expression within the TME, presumably due to increased CD28 signalling, and may promote TI‐Treg suppressive activity. As a result, the combination of anti‐CTLA4 with EZH2 inhibition can act synergistically to engage potent anti‐cancer immunity in murine cancer models …”
Section: Transcription In Ti‐tregmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several epigenetic inhibitors, such as EZH2 and DNMT inhibitors have been shown to improve the efficacy of immunotherapy treatments such as anti-CTLA-4 and anti-PD1 treatment. For example, Goswami et al (2018) showed that modulation of EZH2 expression in T cells improves efficacy of anti-CTLA-4 therapy in vivo [49]. Similarly, the DNMT inhibitor decitabine enhanced lymphocyte migration and function and synergized with CTLA-4 blockade in a murine ovarian cancer model [50].…”
Section: Epitherapy and Combination Therapymentioning
confidence: 99%
“…EZH2 can negatively regulate interferon response genes, T helper cell (TH)-1 type chemokines, and major histocompatibility complex (MHC) expression in tumor cells [4,5]. EZH2 inhibition can enhance tumor immunogenicity through activation of endogenous retroviruses [6] and can modulate immune cell differentiation [7,8]. Therefore, it has been hypothesized that EZH2 inhibitors, which are currently part of clinical studies [9], can overcome resistance to ICB by targeting tumor cells and modulating the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%